Quantitative diet, body composition and sprint performance in female professional beach handball players - Martinez-rod; Martínez-Rodríguez, A.; Sánchez-Sánchez, J.; Martínez-Olcina, M.; Vicente-Martínez, M.; Peñaranda-Moraga, M.; Asencio-Mas, N.; Gonzálvez-Alvarado, L.; Matlosz, P.; Yáñez-Sepúlveda, R.; Cortés-Roco, G.; Sánchez-Sáez, J. A. (Nutrients, 2023)
Women`s elite sports have experienced an exponential increase in the last decade, as has beach handball (BH). The high demands of this sport mean that athletes need to be in superior physical condition, so nutrition and body composition are determining factors in their sporting performance. For this reason, the aim of this study was to analyze, compare and correlate the most relevant variables of food intake (quantitative), body composition (focus on the bone mass characteristics) and sprint performance in female professional BH players. Thirty-three women from the National Spanish Team participated in this study. Dietary assessment, anthropometric measurements and sprint tests were performed. In general, the players had a low carbohydrate intake and adequate protein intake, with no significant differences depending on the category and playing position. For senior players, positive correlations were found between protein intake and bone mass (r = 0.584, p = 0.022), polyunsaturated fatty acid intake and muscle mass (r = 0.387, p = 0.026) and finally between fat mass and animal protein intake (r = 0.569, p = 0.027). Body composition was similar in both categories; however, goalkeepers had the highest fat (22.6 ± 3.86%, 16.2 ± 4.84 kg) component (vs. wings: 17.4 ± 3.53%, p = 0.031/vs. specialists: 11.1 ± 1.91 kg, p = 0.034), and senior players had higher muscle mass (kilograms). It is worth noting the finding that players with a greater trochanter height had significantly lower sprint times (p = 0.014 and p = 0.048 for 5 and 10 m, respectively). Certain bone characteristics, such as iliospinale height, biacromial and bimalleolar diameters, mesosternal perimeter and biceps skinfold, differ depending on the position. In addition, the greater speed of the senior players may be due to the greater specialization, number of training sessions performed and specific bone characteristics, such as trochanter height. In this regard, the data provided in this study will assist with establishing criteria for the selection of talent for this sporting discipline.